Embodied memory: unconscious smiling modulates emotional evaluation of episodic memories - Arminjon, Mathieu; Preissmann, Delphine; Chmetz, Florian; Duraku, Andrea; Ansermet, François; Magistretti, Pierre J. (Frontiers in Psychology, 2015)
Since Damasio introduced the somatic markers hypothesis in 1991, it has spread through the psychological community, where it is now commonly acknowledged that somatic states are a factor in producing the qualitative dimension of our experiences. Present actions are emotionally guided by those somatic states that were previously activated in similar experiences. In this model, somatic markers serve as a kind of embodied memory. Here we test whether the manipulation of somatic markers can modulate the emotional evaluation of negative memories. Because facial feedback has been shown to be a powerful means of modifying emotional judgements, we used it to manipulate somatic markers. Participants first read a sad story in order to induce a negative emotional memory and then were asked to rate their emotions and memory about the text. Twenty-four hours later, the same participants were asked to assume a predetermined facial feedback (smiling) while reactivating their memory of the sad story. The participants were once again asked to fill in emotional and memory questionnaires about the text. Our results showed that participants who had smiled during memory reactivation later rated the text less negatively than control participants. However, the contraction of the zygomaticus muscles during memory reactivation did not have any impact on episodic memory scores. This suggests that manipulating somatic states modified emotional memory without affecting episodic memory. Thus, modulating memories through bodily states might pave the way to studying memory as an embodied function and help shape new kinds of psychotherapeutic interventions.